Da aliança ao democratismo: a trajetória do PFL no Rio Grande do Norte (1985-2006) - Costa, Andrea Maria Linhares da (2012)
This thesis analyzes the political and electoral trajectory of the PFL in Rio Grande do Norte from its beginning in 1985 until his last electoral dispute in 2006, before the process of rebuilding occurred in 2007. The central argument of the thesis is that the PFL occupied side by side with the PMDB the central position in the dynamic of the state partisan politics. This was due to its ability to control the process of disputes for majority positions in the state, especially for Senate vacancies. The hypothesis that support the central argument are related to the trajectory of the formation of the party still under the military regime, where the group that took over the leadership of the party enjoyed privileged conditions for the consolidation of political and electoral power. Another factor associated with their performance was the force that was developed in the second-largest electoral college in the state, Mossoró. To these hypotheses we add the role Jose Agripino Maia who, leading without competitors within the party, concentrated a large power in making decisions in face of adverse contexts to ensure (his) conditions for success in majoritarian disputes